Pulse Improvement Physiological, Molecular and Genetic Perspectives (Springer International Publishing, 2018)
Advances in molecular biology and genome research in the form of molecular breeding and genetic engineering put forward innovative prospects for improving productivity of many pulses crops. Pathways have been discovered, which include regulatory elements that modulate stress responses (e.g., transcription factors and protein kinases) and functional genes, which guard the cells (e.g., enzymes for generating protective metabolites and proteins). In addition, numerous quantitative trait loci (QTLs) associated with elevated stress tolerance have been cloned, resulting in the detection of critical genes for stress tolerance. Together these networks can be used to enhance stress tolerance in pulses. This book summarizes recent advances in pulse research for increasing productivity, improving biotic and abiotic stress tolerance, and enhancing nutritional quality.